A Case-Control Study of the Association of Leptin Gene Polymorphisms with Plasma Leptin Levels and Obesity in the Kerala Population. (28th December 2022) - Manju, Sudharmadevi K.; Anilkumar, Thottathil R.; Vysakh, G.; Leena, Balakumaran K.; Lekshminarayan, Vijayalekshmi; Kumar, Pradeep G.; Shenoy, Trivikrama K.
Abstract : Background . Over the last few years, the importance of leptin in energy metabolism has been extensively studied in both animal models and in humans. Very few results are available on the association between human leptin gene ( LEP ) variants and obesity traits in India. We designed this study to analyse the polymorphisms in human leptin gene and the association of sequence variants with obesity among the population in Kerala, South India. Methods . In this case-control design of 148 study participants, data were collected on socioeconomic aspects and anthropometric measurements. Plasma glucose, insulin, leptin, and lipid profile were measured. Genotyping was done by automated DNA sequencing. Results . The common Single Nucleotide Polymorphism (SNP) of 5′-UTR of LEP  − 2548G/A was found to be present in the study population with "A" variant as dominant allele. A novel synonymous mutation Thr5Thr of exon 2 of LEP was identified in heterozygous form in one subject with morbid obesity with hyperleptinemia. A novel missense mutation Phe17Leu was observed in two subjects with obesity in heterozygous condition. A novel missense mutation Lys36Arg in exon 2 of LEP was observed in one subject with abdominal obesity and decreased serum leptin level. Conclusion . LEP  − 2548G/A at 5′-untranslated region was found to be common with the mutant "A" variant in the study population. SNPs of exons in LEP were found to be rare but associated with morbid obesity and altered levels of serum leptin in the study population in Kerala, India.